Nest size is not closely related to breeding success in Blue Tits: A long-term nest-box study in a Mediterranean oak habitat. (10th February 2016) - Lambrechts, Marcel M.; Marrot, Pascal; Fargevieille, Amélie; Giovannini, Pablo; Lucas, Annick; Demeyrier, Virginie; Midamegbe, Afiwa; Perret, Philippe; Grégoire, Arnaud; Charmantier, Anne; Doutrelant, Claire
Abstract: Various components of breeding success are predicted to be related to avian nest size because (1) some individuals are physically able to build larger nests than other individuals or (2) larger nests provide more protection in the absence of predation than smaller nests. The results of an 18-yr correlative nest-box study in Blue Tits ( Cyanistes caeruleus ) show that nest size is not closely related to components that reflect breeding performance, after controlling for other female characteristics (first-egg date, clutch size, and female age) assumed to influence breeding performance in long-term studies. Our results support those of most short-term field studies that have reported weak associations between nest size and breeding performance in cavity-nesting passerines. We suggest that the absence of an association between nest size and breeding performance can be explained by the fact that the vast majority of nest-box studies have used small nest chambers that imposed physical constraints on the full expression of the nest. We recommend using a larger range of nest-chamber sizes that better reflect the characteristics of natural holes exploited by secondary cavity-nesting species.